Effect of vitamin D deficiency and supplementation on myocardial deformation parameters and epicardial fat thickness in patients free of cardiovascular risk - ÇİNÇİN, AHMET ALTUĞ; ATAŞ, HALİL; SARI, İBRAHİM; SÜNBÜL, MURAT (SPRINGER, 2015)
Vitamin D deficiency is associated with impaired myocardial deformation parameters and cardiovascular disease (CVD). Increased epicardial fat thickness (EFT) is also associated with increased risk of CVD. The aim of the study is to evaluate the effect of vitamin D deficiency and supplementation on myocardial deformation parameters and EFT. The study population consisted of 50 patients with vitamin D deficiency who were free of cardiovascular risk (mean age: 42.6 +/- A 8.9 years, 37 female). Patients were treated with oral administration of vitamin D3. Myocardial deformation parameters and EFT were evaluated before and after treatment of those patients. Vitamin D levels significantly increased after treatment (30.5 +/- A 10.5 vs. 9.9 +/- A 5.3 nmol/l, p < 0.001). There was no significant difference between conventional echocardiographic parameters before and after treatment. Baseline EFT was significantly higher than post-treatment measurements (35.2 +/- A 8.0 vs. 27.5 +/- A 5.6 mm, p < 0.001). Post-treatment myocardial deformation parameters were also significantly higher than baseline measurements. Baseline vitamin D levels correlated with baseline EFT and left ventricular global longitudinal strain (LV-GLS). Post-treatment vitamin D levels also correlated with post-treatment EFT, body mass index, and LV-GLS. Baseline vitamin D level was an independent predictor of baseline LV-GLS (p = 0.002). Patients with impaired LV-GLS had significantly lower vitamin D levels than patients with normal LV-GLS (6.6 +/- A 3.8 vs. 11.0 +/- A 5.3 nmol/l, p = 0.005). Baseline vitamin D level was also an independent predictor of baseline impaired LV-GLS (p = 0.010). Vitamin D supplementation has beneficial effects on myocardial deformation parameters and EFT. Moreover, baseline vitamin D levels are a predictor of impaired LV-GLS.
Keywords: Vitamin D deficiency; Epicardial fat thickness; Myocardial deformation; Cardiovascular risk; 2-DIMENSIONAL SPECKLE-TRACKING; VENTRICULAR DYSSYNCHRONY; CARDIAC-HYPERTROPHY; ADIPOSE-TISSUE; STRAIN; ECHOCARDIOGRAPHY; DYSFUNCTION; PREVENTION; GUIDELINE; DISEASE